Siyāsah Maliyah Analysis of West Java Governor's Rereongan Sapoe Sarebu Movement Policy in Batununggal District - Saputra, Aditya Gustian; Saebani, Beni Ahmad; Pelita, Bobang Noorisnan (Program Studi Studi Agama-Agama Pascasarjana UIN Sunan Gunung Djati Bandung, 2026)
This study analyzes the Rereongan Sapoe Sarebu (Poe Ibu) Movement policy from a siyasah maliyah perspective and evaluates its effectiveness in enhancing community welfare. Employing a qualitative empirical juridical approach, it draws on in-depth interviews, field observations, and documentation from Batununggal District, Bandung City. Findings reveal strong normative legitimacy for Poe Ibu within Indonesian positive law and Islamic jurisprudence, embodying maslahah (welfare), distributive justice, and social solidarity. However, sub-district implementation falters due to administrative hurdles, poor inter-agency coordination, and technical misalignment. In contrast, educational institutions show notable success in boosting social participation and solidarity, despite community debates and obstacles. From a siyasah maliyah viewpoint, the policy is justifiable if voluntary, transparent, and supplementary to state welfare duties. Recommendations include strengthening regulations, transparency, and accountability to ensure optimal, sustainable implementation aligned with social justice.